2010
DOI: 10.1093/nar/gkq1186
|View full text |Cite
|
Sign up to set email alerts
|

The suboptimal structures find the optimal RNAs: homology search for bacterial non-coding RNAs using suboptimal RNA structures

Abstract: Non-coding RNAs (ncRNAs) are regulatory molecules encoded in the intergenic or intragenic regions of the genome. In prokaryotes, biocomputational identification of homologs of known ncRNAs in other species often fails due to weakly evolutionarily conserved sequences, structures, synteny and genome localization, except in the case of evolutionarily closely related species. To eliminate results from weak conservation, we focused on RNA structure, which is the most conserved ncRNA property. Analysis of the struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 19 publications
2
34
0
Order By: Relevance
“…29 The presence of 6S RNAs in Actinobacteria has been previously addressed. Pan ek et al 31 used suboptimal structures to find 6S RNAs and reported candidates in Streptomyces and Mycobacterium. The candidate 6S RNA of M. smegmatis did not bind to the s 70 -RNAP homolog of this bacterium, as inferred from co-immunoprecipitation experiments.…”
Section: Resultsmentioning
confidence: 99%
“…29 The presence of 6S RNAs in Actinobacteria has been previously addressed. Pan ek et al 31 used suboptimal structures to find 6S RNAs and reported candidates in Streptomyces and Mycobacterium. The candidate 6S RNA of M. smegmatis did not bind to the s 70 -RNAP homolog of this bacterium, as inferred from co-immunoprecipitation experiments.…”
Section: Resultsmentioning
confidence: 99%
“…At least one RNA identified based on its structural similarity to 6S RNA (Ms1 RNA in Mycobacterium smegmatis ) does not bind to the holoenzyme form of RNA polymerase, although it does interact with core RNA polymerase (60, 61). This example serves as a cautionary tale in relying too heavily on secondary structure as the predictor of 6S RNA candidates, but also raises the intriguing possibility that there are additional classes of sRNAs that function through interaction with RNA polymerase using different mechanisms.…”
Section: S Rnas Are Widespread Throughout the Bacterial Kingdommentioning
confidence: 99%
“…A bioinformatics search based on matching for energetically suboptimal structures recently identified the M. smegmatis homolog of MTS2823 as a potential 6S RNA candidate, but lack of binding to RNA polymerase led the authors to conclude that it is not a genuine 6S RNA, 86 and so far no 6S RNA homolog has been identified in mycobacteria. It remains to be determined if MTS2823 is a conventional sRNA that acts via base-pairing with specific mRNA targets or with protein or whether its mode of action differs entirely from other sRNAs.…”
Section: Tuberculosis Intergenic Srnas and Stressmentioning
confidence: 99%